Evaluating policy coherence and integration for adaptation: the case of EU policies and Arctic cross-border climate change impacts - Kivimaa, Paula; Hildén, Mikael; Carter, Timothy R.; Mosoni, Claire; Pitzén, Samuli; Sivonen, Marja Helena (Taylor & Francis, 2025)
Abstract The impacts of climate change materialize in different ways and are of varying magnitudes at different locations around the world. Adaptation is a global policy challenge because some of those impacts propagate across borders. The presence of borders influences the policy responses that may aim at preventing, alleviating, or exploiting the impacts. Yet the dynamics of responses to cross-border impacts have not been explored in research on policy coherence. We extend the analysis of climate policy coherence and integration to cover adaptation policies that are enacted at different but interacting geographical locations, proposing a conceptual approach how to do this. We illustrate our approach with examples of European Union (EU) policies related to the cross-border ramifications of climate change impacts originating in the Arctic. Our example highlights interconnections between climate change adaptation policy with foreign, security and trade policies. Since climate change impacts are transmitted through systems that cross borders, policymakers in the EU and elsewhere should recognize the links between policy domains with potential significance in responding to these propagating impacts. The policy responses of a recipient region at risk of such impacts are limited by jurisdictional borders. By explicitly recognizing elements of integration and coherence, more effective policy actions can be developed. Seeking coherence between climate and other policies between different regions, intertwined together via global networks of trade and other relations, should be a fundamental policy goal for the EU. Key policy insights • New policies are needed to address the climate change impacts that are transmitted across jurisdictional borders. • Coherence across policy domains that deal with cross-border issues helps in planning effective policy actions to address the challenges posed by cross-border climate change impacts. • Integration of climate policy into other policy domains facilitates policy coherence by ...